2013
DOI: 10.1155/2013/928601
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: Immunopathogenesis and Immunological Markers

Abstract: Sarcoidosis is a multisystem granulomatous disorder invariably affecting the lungs. It is a disease with noteworthy variations in clinical manifestation and disease outcome and has been described as an “immune paradox” with peripheral anergy despite exaggerated inflammation at disease sites. Despite extensive research, sarcoidosis remains a disease with undetermined aetiology. Current evidence supports the notion that the immune response in sarcoidosis is driven by a putative antigen in a genetically susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 117 publications
2
49
0
3
Order By: Relevance
“…The cause of sarcoidosis is a complex immune paradox consisting of a localized hyperinflammatory environment coupled with peripheral anergy (39). Despite the evidence that granulomas form in response to persistent antigen stimulation (40), and that this antigen is likely bacterial in origin (10), most work on sarcoidosis has centered on T cells and, to a lesser extent, tissue macrophages and dendritic cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of sarcoidosis is a complex immune paradox consisting of a localized hyperinflammatory environment coupled with peripheral anergy (39). Despite the evidence that granulomas form in response to persistent antigen stimulation (40), and that this antigen is likely bacterial in origin (10), most work on sarcoidosis has centered on T cells and, to a lesser extent, tissue macrophages and dendritic cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies suggest that development of sarcoidosis involves an interplay between extrinsic antigens, genetic factors, and immune responses. 16,17 The regulation of immune mechanisms is more complex and extensive than can be discussed in this article, 18 but researchers have suggested that poorly degraded antigen is engulfed by antigen-presenting cells (APCs) and displayed on the APCs' major histocompatibility complex (MHC). 10,18 A CD41 T-cell receptor attaches to this antigen-MHC complex and becomes activated.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…16,17 The regulation of immune mechanisms is more complex and extensive than can be discussed in this article, 18 but researchers have suggested that poorly degraded antigen is engulfed by antigen-presenting cells (APCs) and displayed on the APCs' major histocompatibility complex (MHC). 10,18 A CD41 T-cell receptor attaches to this antigen-MHC complex and becomes activated. The result is a release of cytokines, including interleukin (IL)-2, which induce clonal proliferation of activated, strongly Th1 polarized T-helper cells that secrete proinflammatory cytokines, such as IL-2, IL-12, and IL-18 (interferon-gamma-inducing factor), which facilitate granuloma formation.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…С аркоидоз -системная патология иммунной системы, характеризующаяся образованием эпителиоидно-клеточных неказеифицирующихся гранулем и иммунным парадоксом, проявляю-щимся избыточной клеточной реакцией в местах проявления болезни при периферической анергии [1]. Однако выявление саркоидной гранулемы вне связи с конкретной клинической ситуацией не позво-ляет установить диагноз «саркоидоз».…”
Section: обзорыunclassified